The stylistic references to the Andalusian meadow poem in describing the Al-Ghandaq River as the “losha” of Andalusia - Bourahla, Nabila; Bendahoua, Khaira (Journal of Human Sciences, 2023)
This article aims to make a stylistic approach through a poem by Marj al-Khal in describing the Gannada River in the town of Balusha, in which the poet excelled, by highlighting some of the aesthetic aspects of the Andalusian nature, which formed a milestone in the poets’ use of the various manifestations that colored Andalusia and made poets wander in the magic of nature out of nowhere. From this perception, this article came as an embodiment of natural phenomena by standing on the structural, grammatical, semantic and rhetorical structures that included the topography of the poem describing the Al-Ghandaq River.